2018
DOI: 10.1152/ajplung.00308.2017
|View full text |Cite
|
Sign up to set email alerts
|

The neutrophil chemoattractant peptide proline-glycine-proline is associated with acute respiratory distress syndrome

Abstract: ARDS is characterized by unrelenting PMN inflammation and vascular permeability. The matrikine proline-glycine-proline (PGP) and acetylated PGP (Ac-PGP) have been shown to induce PMN inflammation and endothelial permeability in vitro and in vivo. In this study, we investigated the presence and role of airway PGP peptides in acute lung injury (ALI)/ARDS. P. aeruginosa-derived LPS was instilled intratracheally (i.t) in mice to induce ALI and increased Ac-PGP with neutrophil inflammation was noted. The PGP inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Our healthy controls did not have Ac-PGP measurements. Nevertheless, our previous studies have shown absent or extremely low levels of Ac-PGP in healthy lung airway fluid [64]. It has been reported that BAL samples obtained from separate geographic regions within the same lung can demonstrate highly dissimilar microbial communities [33,65].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our healthy controls did not have Ac-PGP measurements. Nevertheless, our previous studies have shown absent or extremely low levels of Ac-PGP in healthy lung airway fluid [64]. It has been reported that BAL samples obtained from separate geographic regions within the same lung can demonstrate highly dissimilar microbial communities [33,65].…”
Section: Discussionmentioning
confidence: 82%
“…Next, we measured the levels of Ac-PGP, a collagen breakdown matrikine peptide that is known to upregulate neutrophil chemotaxis and increase lung vascular permeability [35,36]. We found that Ac-PGP was elevated (p = 0.03) in the allograft as compared to native lungs (Fig.…”
Section: Differences Between the Allograft And Native Lung Microbiomementioning
confidence: 90%
“…NET presence was found to be elevated in acute respiratory distress syndrome (ARDS) patients with ventilator-associated pneumonia compared to ARDS alone, and correlated with both bacterial burden and CXCL8 [81]. Considering that MPO has been found to be elevated in the airways of ARDS patients [82] and that this enzyme is associated with lung damage in CF [83,84], NET-associated MPO may be a contributing factor in progression of disease in ARDS. Studies of NETosis are also contributing to a better understanding of neutrophil plasticity.…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…Recent scientific reports provide information on the role of glyprolines in chronic inflammation. N‐acetylated PGP participates in the immune response as a neutrophil chemoattractant in lung diseases (COPD and cystic fibrosis), IBD, ischemic brain stroke as well as chorioamnionitis. Apart from proinflammatory activity, numerous beneficial effects of proline‐containing short sequences were observed.…”
Section: Biological Activity Of the Collagen‐derived Glyprolinesmentioning
confidence: 99%
“…Some of the airway disorders may be accompanied by impaired endothelial cell integrity. PGP has been shown to participate in the deregulation of vascular permeability as a result of activation of CXCR2 receptors on endothelial cells. Both local and systemic administration of PGP led to increased vascular leakage of pulmonary vessels similar to that caused by lipopolysaccharide present in the cell membrane of Gram‐negative bacteria strains.…”
Section: Biological Activity Of the Collagen‐derived Glyprolinesmentioning
confidence: 99%